Pharmacokinetics and pharmacodynamics of an extrafine fixed pMDI combination of beclometasone dipropionate/formoterol fumarate in adolescent asthma. (1st June 2015) - Kuna, Piotr; Govoni, Mirco; Lucci, Germano; Scuri, Mario; Acerbi, Daniela; Stelmach, Iwona
<x xml:space="preserve">Abstract</x> Aim The aim was to investigate the pharmacokinetics and pharmacodynamics of an extrafine pressurized metered‐dose inhaler (pMDI) fixed combination of beclometasone dipropionate (BDP)/formoterol fumarate (FF) in adolescent and adult asthma. Methods This was a three‐way crossover study, on 30 asthmatic adolescents receiving BDP/FF pMDI with or without a valved holding chamber (VHC) or a free licenced combination of BDP pMDI and FF pMDI plus a parallel arm of 30 asthmatic adults receiving BDP/FF pMDI. All patients received a single dose of BDP and FF of 400 µg and 24 µg, for each treatment, respectively. Assessments were performed over 8 hours. Results In adolescents, the 90% confidence intervals (CIs) for the systemic exposure (AUC(0, t)) geometric mean ratio of the fixed combination with or without VHC vs. the free combination were within the bioequivalence range 0.80–1.25, both for beclometasone‐17‐monopropionate (B17MP, the active metabolite of BDP) and formoterol. Pharmacodynamic variables for plasma potassium and glucose, pulse rate and pulmonary function in adolescents were equivalent between treatments, 95% CI within 0.9, 1.09. The upper level of 90% CIs for AUC(0, t) geometric mean ratio adolescents : adults of B17MP and formoterol after treatment with BDP/FF pMDI was lower than 1.25, 90% CI 0.78, 1.04 and 0.86, 1.17, respectively. Conclusions In adolescents the pharmacodynamics and the overall systemic exposure to the active ingredients of an extrafine fixed combination of BDP/FF pMDI with or without a VHC was equivalent to that of a free licenced combination of pMDIs of established safety and efficacy profiles. The systemic exposure in adolescents was not higher than in adults. These results support the indication for use of inhaled corticosteroid/long acting β2‐adrenoceptor agonist pMDIs in adolescents at the same dosage as in adults.